2021
DOI: 10.3389/fcvm.2020.614129
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the Electrocardiogram in Japanese Fabry Patients Under Long-Term Enzyme Replacement Therapy

Abstract: Objective: An electrocardiogram (ECG) is an important tool for demonstrating cardiac manifestations in various heart diseases. The present study clarified the characteristics of ECG parameters in Japanese Fabry patients under long-term enzyme replacement therapy (ERT).Methods: We analyzed the ECGs of 40 Fabry patients (male, n = 17; female, n = 23) before and after treatment with ERT. To evaluate the atrio-ventricular conduction, the PQ interval, corrected PQ and PQ minus P-wave in lead II (Pend-Q) were calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…This effect of treatment (ERT) on the electrophysiological parameters cannot be studied given the small untreated patient sample, the treatment indication bias and the vast difference in age at which treatment was started between patients. Previous studies indicated that cardiac disease may progress despite ERT [19,42], and this is confirmed by the current study. The data from the current study, can, however, be used to analyze the effect of new FD therapies to see if they outperform current treatment in preventing the progression of cardiac disease.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This effect of treatment (ERT) on the electrophysiological parameters cannot be studied given the small untreated patient sample, the treatment indication bias and the vast difference in age at which treatment was started between patients. Previous studies indicated that cardiac disease may progress despite ERT [19,42], and this is confirmed by the current study. The data from the current study, can, however, be used to analyze the effect of new FD therapies to see if they outperform current treatment in preventing the progression of cardiac disease.…”
Section: Discussionsupporting
confidence: 90%
“…Previous cross-sectional and longitudinal studies with a relatively small sample size show that early ECG abnormalities in FD patients include a short PR-interval and bradycardia [18,19]. A long P-wave duration, prolonged QRS-duration, QTc, high QRS-amplitude, Twave inversion and left frontal QRS-axis deviation may occur in later disease stages [19][20][21].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Furthermore, from the results of our study, not the criterion used in LVH diagnosis of a Sokolow-Lyon index (SV1 + RV5) of ≥3.5 mV but the value of voltage (upper limit at 95% CI of 3.9 mV in non-FD patients) of ≥4.0 mV seemed to be better for raising the pretest probability for detection of FD. In Morimoto's study, their data showed that the majority of the male FD patients with LVH had SV1 + RV5 voltage of ≥4.0 mV [22]. When we focused on LVH patients with LVEF < 50% in our study cohort, there was only one patient with FD and that patient showed sinus rhythm and SV1 + RV5 > 4.0 mV with a strain pattern.…”
Section: Discussionmentioning
confidence: 88%
“…Namdar et al reported that Pend-Q interval < 40% was a highly sensitive and specific marker in the differentiation of FD among patients with LVH [13]. Furthermore, Morimoto et al recently reported the characteristics of an ECG in Japanese Fabry patients who were receiving long-term enzyme replacement therapy: shortening of the PQ interval and Pend-Q was seen in 7.5% and 47.5% of 40 FD patients, respectively [22]. These results suggest that shortening of Pend-Q seems to be a more important finding in FD patients.…”
Section: Discussionmentioning
confidence: 99%